Study the Effect of Palm Date Extract against Bacterial and Fungal Species Isolated from Ear Infection (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
A number of bacterial and fungal strains associated with external ear infections from the Samarra General Hospital were isolated and included bacterial species (Escherichia coli, Streptococcus pneumonia, Klebsiella spp, Staphylococcus aureus, Pseudomonas aeruginosa) and fungal species.  (Aspergillus flavus, Aspergillus niger, Pencillium spp, Cladosporium) The genus Phoenix doctitera is an important and rich variety of nutrients. It has been tested as a subject for study. Its biological effect on pollen was tested against bacterial and fungal species using ethanol and distilled distilled water. The results showed an inhibitory effect against some of the above-mentioned species with the highest inhibitory against Staphyiococcus .aureus 0.25 ± 2.23 mm and the highest inhibition of Cladosporium 0.2 ± 2.0 mm. Bacteria resistance E.coli, Klebsiella and A. fungus A. flavus , A. niger for the extract of alcohol as the water extract did not have any effect against bacterial and fungal species.